Seafloor Geomorphology and Processes on the Western Continental Margin of India based on Multibeam Acoustic Backscatter Data Analysis. Issue 2 (4th March 2018) - Dandapath, Sumanta; Menezes, Andrew; Chakraborty, Bishwajit; Kurian, John; Raju, Koppella N. Prudhvi
ABSTRACT: An assessment of the multibeam sonar data of the central Western Continental Margins of India has been carried out to evaluate the seafloor geomorphology and processes by examining the geomorphological attributes e.g., slope, sediments, structures, etc. associated with geomorphic features. The variation in relief and the features located in the region have been mapped and interpreted collectively by utilizing several geospatial mapping tools. The backscatter strength across the area, apparently congruent with the local relief, has helped to examine the sediment movement on the seafloor. The prominent features found in the region include faults, pockmarks, mounds, submarine terraces, and submerged fossil reefs. Several areas with varying topography engender comparable fractal dimension at short scale breaks, and the probability density functions (PDFs) utilizing backscatter data depicting overlapping classes. The present study highlights how fractals and scale break parameters can be utilized to determine the seafloor processes and associated sedimentological dynamics in a complex geographical environment with strong bottom currents, seasonal upwelling, and faulted structure. The role and impact of the various geomorphic processes on the reworking of sediment movement and the overall progression of the seafloor morphology has been revealed for the first time in this part of the ocean bottom.